Study of Bare and Mercury‐Coated Vibrated Carbon, Gold and Silver Microwire Electrodes for the Determination of Lead and Cadmium in Seawater by Anodic Stripping Voltammetry. Issue 2 (10th January 2013) - Bi, Zhaoshun; Salaün, Pascal; van den Berg, Constant M. G.
Abstract Carbon, gold and silver microwires are revisited under vibrated conditions for detection of trace lead and cadmium in seawater. The Pb and Cd peaks fully overlapped on the bare gold and carbon electrodes and partially on the silver electrode. The sensitivity of all three was insufficient for detection in uncontaminated waters. Peak separation was obtained after coating with mercury (Hg). Only the Hg‐coated silver electrode is suitable when preplated. Limits of detection for Pb using the Hg/C and Hg/Ag electrodes (20–40 pM), and Cd (70 pM), are sufficiently low for Pb and Cd detection in seawater.